ULÍWMA BILIMLENDIRIW MEKTEPLERINDE TEXNOLOGIYA PÁNIN OQÍTÍWDA USHÍRASATUǴÍN MASHQALALAR HÁM OLARDÍ SAPLASTÍRÍW JOLLARÍ - Kurmanov, A.P. (SCIENCE and SOCIETY, 2024)
This article is devoted to the actual problems of teaching the discipline "Technology" in Uzbekistan schools. The author discusses several main problems that affect the effectiveness of teaching this discipline: lack of motivation of students, outdated equipment, insufficient number of lessons, outdated content of curricula, as well as the impossibility of an individual approach to the student.